BIOMARKERS AS PROXIES FOR PLANT INPUTS TO PEATS: AN EXAMPLE FROM A SUB-BOREAL OMBROTROPHIC BOG - Pancost R.D.; Baas M.; van Geel B.; Sinninghe Damste J.S. (My University, 2002)
Lipid distributions in modern peat-forming plants were determined and compared to biomarkers recovered from a ca. 2800 year old peat deposited in a Dutch ombrotrophic bog. The peat section spans a well-constrained shift in local hydrology and vegetation, and potential molecular proxies for plant inputs were directly tested against the macrofossil record. Based on the analyses of modern plants, low-molecular-weight (LMW) n-alkanes (C23, C25) and high-molecular-weight n-alkanes (C33) are proposed as potential biomarkers for Sphagnum and non-Sphagnum inputs, respectively. Consistent with this, in the Bargerveen peat core, LMW n-alkane abundances increase and HMW n-alkane abundances decrease coincident with the shift to Sphagnum dominated peat. Additional potential proxies include the abundances of C22 α,ω-alkanedioic acid and phytenyl phytenoate as Sphagnum indicators and the abundances of the triterpenoids taraxer-14-ene and taraxast-20-ene as biomarkers for Ericaceae rootlets.